A protocol for cluster confirmations of SDN controllers against DDoS attacks. (July 2021) - Iranmanesh, Amir; Reza Naji, Hamid
Highlights: PATGEN: a protocol to reduce the effects of DDoS attacks using an advanced genetic algorithm with optimized and new operators. PATGEN is possible without using external resources. PATGEN improves load balancing. Significant improvement in SDN performance as compared to existing works. Abstract: Software-Defined Networking (SDN) makes it easier to manage the network by separating the Data plane and Control plane, but these networks are susceptible to DDoS attacks. Most well-known algorithms for reducing the effects of DDoS attacks are based on SDN traffic analysis and prediction. Their main problems are false positive/negative results. Therefore, we propose PATGEN, a Protocol to reduce the effects of DDoS ATtacks using an advanced GENetic algorithm with optimized and new operators, thereby significantly reducing the effects of attacks and increasing the efficiency of the multi-controller SDN. Using the robust initial population procedure increases the convergence speed of the algorithm. Unlike other methods, PATGEN is possible without using external resources. Experimental results show that PATGEN increases the throughput and reduces the average delay compared to states of the art methods.